2001
DOI: 10.1142/s021812740100295x
|View full text |Cite
|
Sign up to set email alerts
|

Master–slave Synchronization of Lur'e Systems With Time-Delay

Abstract: In this paper time-delay effects on the master-slave synchronization scheme are investigated. Sufficient conditions for master-slave synchronization of Lur'e systems are presented for a known time-delay in the master and slave systems. A delay-dependent synchronization criterion is given based upon a new Lyapunov-Krasovskii function. The derived criterion is a sufficient condition for global asymptotic stability of the error system, expressed by means of a matrix inequality. The feedback matrix follows from so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
152
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(156 citation statements)
references
References 30 publications
4
152
0
Order By: Relevance
“…21 This Lyapunov-Krasovskii functional is more general than the more "classical" LyapunovKrasovskii functionals employed in other work. 10,17 As a consequence of this greater generality, the result of Theorem 1 is less conservative than results that would have been obtained using the more classical functionals.…”
Section: Remarkmentioning
confidence: 94%
See 1 more Smart Citation
“…21 This Lyapunov-Krasovskii functional is more general than the more "classical" LyapunovKrasovskii functionals employed in other work. 10,17 As a consequence of this greater generality, the result of Theorem 1 is less conservative than results that would have been obtained using the more classical functionals.…”
Section: Remarkmentioning
confidence: 94%
“…Pyragas 9 considered the synchronization of two directionally coupled Mackey-Glass systems. Yalçin et al 10 discussed the ͑nonan-ticipative͒ master-slave synchronization of time-delayed Lur'e systems, and the results obtained were later generalized. 11,12 Senthilkumar and Lakshmanan 13 discussed the transitions from anticipating synchronization to lag synchronization via complete synchronization of time-delay systems with two time delays.…”
Section: Introductionmentioning
confidence: 99%
“…Guo and Zhong in [6] and Yalcin et al in [21] derived some delay-independent [9] and delay-dependent synchronization criteria for global asymptotic stability of the error system, which are expressed as LMIs and derived from extended LKFs. Liao and Chen [11] and Cao et al [1] further generalized and improved the results in [21] and employed model transformation, which leads to some conservative synchronization criteria for inducing additional terms.…”
Section: Introductionmentioning
confidence: 99%
“…Guo and Zhong in [6] and Yalcin et al in [21] derived some delay-independent [9] and delay-dependent synchronization criteria for global asymptotic stability of the error system, which are expressed as LMIs and derived from extended LKFs. Liao and Chen [11] and Cao et al [1] further generalized and improved the results in [21] and employed model transformation, which leads to some conservative synchronization criteria for inducing additional terms. Shortly, some new approaches are employed to avoid using model transformation and derive much less conservative synchronization conditions, for example, Xiang et al [20], He et al [8] used integral inequality [22] in the derivative of Lyapunov functional respectively, and it turned out that the permissible delay threshold can be fairly enlarged both in theory and in numerical experiment.…”
Section: Introductionmentioning
confidence: 99%
“…This type of coupling has been widely used to investigate synchronization problems in various fields such as electric circuit [53,54], coupled pendulums [55], delayed neural networks (DNNS) [56], and general models [57][58][59][60][61][62][63]. In a recent paper, we have showed that the former type of delayed coupling can enhance spatiotemporal order in coupled neuronal systems [40].…”
Section: Introductionmentioning
confidence: 99%